Aluminum Foil Based Fatigue Sensor for Structural Health Monitoring of Carbon Fiber Composites. (2015) - Burkov, Mikhail; Panin, Sergey; Lyubutin, Pavel; Eremin, Alexander; Maruschak, Pavlo; Menou, Abdellah
Abstract: For the development of a technique for cyclic deformation assessment using aluminum foil sensors glued onto the specimen surface the fatigue tests of carbon fiber reinforced polymer (CFRP) specimens were carried out. The DSLR camera mounted onto an optical microscope was used for capturing the images of sensors to reflect strain induced relief, which than was numerically estimated using various informative parameters in order to obtain the cyclic deformation assessment of composite. The results are discussed in view of application of this method for the development of Structural Health Monitoring (SHM) approach.